From awareness to action: The mediating role of personal values in shaping sustainable entrepreneurship intentions - Saraswati, Nindya; Assyofa, Allya Roosallyn; Meirani, Nadia (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Despite growing concern over environmental issues, the psychological mechanisms that translate awareness into sustainable entrepreneurial action remain underexplored. This study explores the relationship between environmental awareness and sustainable entrepreneurship intentions, focusing on the mediating role of personal values. A quantitative survey was conducted among 175 entrepreneurship students in West Java, Indonesia, using structural equation modelling (SEM). The results reveal that personal values significantly mediate the relationship between environmental awareness and sustainable entrepreneurship intentions. Specifically, individuals with strong biospheric and altruistic value orientations exhibit a more pronounced link between environmental concern and entrepreneurial intent. Furthermore, the study demonstrates the effectiveness of SEM in capturing complex psychological dynamics within sustainability-focused entrepreneurship research. Although geographically limited, this study provides a valuable methodological contribution and serves as a reference point for future investigations in emerging market contexts. These findings highlight the importance of integrating value-based components into entrepreneurship education to foster deeper and more sustainable engagement. By addressing a notable gap in current literature, particularly in developing economies, the study offers actionable insights for educators, policymakers, and program designers seeking to promote sustainable entrepreneurship through personal value development.